Transitional signal error on xtudents’ paragraph writing - Ismail, Abbul Kadir; Adjud, Muslimah S. (English Education Department, 2022)
This research aims to know error analysis in using transition signal on students’ Paragraph Writing. The subjects of this research were sixth semester students of Institut Agama Islam Negeri Sultan Amai Gorontalo. English Education Department, in academic year 2018/2019, consisted of 20 students. The method used in this research was a qualitative method with a descriptive design. Technique of collecting data was carried out through interview. Data analysis was performed through data reduction, data presentation, and drawing conclusions. The results showed that the types of error in using transition signal that existed in Paragraph Writing namely; punctuation for transition signal, sentence and clause connectors, types of transition signal, placement of transition signal and repetitive transition signal. The implication of this research was students did not have good competence in using transition signal according to their function and grammar, but some transition signals were still used inappropriately.